Nilai Pendidikan Karakter Sajak “Bulan Ruwah” Karya Subagio Sastrowardoyo dalam Pembelajaran Sastra - Sugeng Supriyono; Nugraheni Eko Wardani; Kundharu Saddhono (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
Poetry as a literature work which is a manifestation of human culture that is full of life value, so it is very relevant for character building. The aim of this research is to describe character value and how to implemented on literature study at school of poetry “Bulan Ruwah” from Subagio Sastrowardoyo. This qualitative research applies the description method and using content analyisis. The data of this research is Subagio Sastrowardoyo’s poetry “Bulan Ruwah”. The data analysis techique was referenced technique and recorded technique, using stylistic approach. It is found that there are three values of characters in the poetry “Bulan Ruwah”.